Complaints Matter: Seriousness of Elder Mistreatment Citations in Nursing Homes Nationwide. (April 2022) - Liu, Pi-Ju; Caspi, Eilon; Cheng, Ching-Wei
Mistreatment of nursing home residents is prevalent and leads to harmful consequences. The Centers for Medicare & Medicaid Services's (CMS) mission to protect residents' right to be free from mistreatment is implemented partially through state survey agencies' (SSAs) issuance of deficiency citations. The goal of this study was to compare SSA standard surveys and SSA complaint investigations with regard to the seriousness (scope and severity) of the mistreatment citations issued. A cumulative link mixed model was built to estimate the differences between standard surveys and complaint investigations in the seriousness of four core and two secondary mistreatment citations nationwide from 2014 to 2017. In all of the six mistreatment deficiency citations, complaint investigations were more likely to be determined as more serious compared with standard surveys. The findings reinforce the importance of strengthening nursing homes' and CMS/SSA response to consumers' concerns and grievances before they escalate into more harmful mistreatment.